Design and development of coconut de-husking machine - Mohammad Shaharom, Muhammad Azreen (2025)
In Malaysia, the coconut industry faces challenges related to the labor-intensive and hazardous de-husking process. This project aims to design and develop a coconut de-husking machine to address these issues. The main objectives are to enhance the efficiency, safety, and cost-effectiveness of the de-husking process. The proposed machine will be designed using SolidWorks 2023 and powered by a single motor. Key methodologies include the conceptual design, engineering analysis, and fabrication of the machine. The expected outcomes are improved processing speed, reduced labor costs, and enhanced worker safety. This project not only aims to benefit the local coconut industry but also has the potential to contribute to global agricultural practices